Albali Cardholder's Attitudes and Behaviors - Nazarov, Javid (My University, 2015)
The purpose of this study is to examine Albali cardholders' attitudes, their owning and usage behaviors, as well as their responses towards loyalty programs. In particular, awareness level of customers about the card, its usage, functions and overall cardholder purchasing patterns are investigated. Data for this study was collected through in-depth interviews and via a questionnaire that was conducted among 151 Albali cardholders across Azerbaijan. The academic framework review and empirical analysis performed for the purposes of this study, lead to a number of strategic recommendations.
Business Consulting Project for UniBank
Keywords: Business; Banking -- Azerbaijan; Credit cards -- Azerbaijan; Credit cards -- Albali -- Azerbaijan; Brand Awareness -- Azerbaijan